2009
DOI: 10.1143/jjap.48.04c141
|View full text |Cite
|
Sign up to set email alerts
|

InN Nanocolumns Grown on a Si(111) Substrate Using Au+In Solid Solution by Metal Organic Chemical Vapor Deposition

Abstract: InN nanocolumns were grown on a gold-coated Si(111) substrate by metal-organic chemical vapor deposition (MOCVD). Herein, indium predeposition was performed before InN nanocolumn growth. The InN nanocolumns were obtained by forming Au+In solid solution droplets on the Au-coated substrate and subsequently nitriding these droplets. In this study, we investigated the morphological properties of InN nanocolumns by changing the growth conditions such as growth temperature, trimethylindium (TMI) flow rate, and growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…InN nanostructures such as nanowires, nanotubes, and nanocolumns have attracted considerable attention because the quantum confinement effect may yield novel functions and improved performance [20]. Lee et al [21] reported the predeposition of In before the growth of InN nanocolumns; InN nanocolumns were obtained by forming droplets of Au + In solid solution on Au-coated substrates following by nitriding these droplets.…”
Section: Introductionmentioning
confidence: 99%
“…InN nanostructures such as nanowires, nanotubes, and nanocolumns have attracted considerable attention because the quantum confinement effect may yield novel functions and improved performance [20]. Lee et al [21] reported the predeposition of In before the growth of InN nanocolumns; InN nanocolumns were obtained by forming droplets of Au + In solid solution on Au-coated substrates following by nitriding these droplets.…”
Section: Introductionmentioning
confidence: 99%